1999
DOI: 10.1620/tjem.187.285
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Confirmation of the Translocation between Chromosome 15 and Y-Chromosome by Fluorescence in situ Hybridization.

Abstract: A 30-year-old woman and her husband visited our hospital with habitual abortion as the complaint. Chromosome examination revealed a normal 46, XX for her and 46, XY, 15, der (15) t (Y; 15) (q12; p12) for him. After her pregnancy amniocentesis was performed. The karyotype was 46, XX, 15, der (15) t (Y; 15) (q12; p12) pat. ish der (15) (DYZ1+). A female baby was delivered. The growth of the baby was normal at 12 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…To our knowledge, this study constitutes (1) the first reported case of a der(15)t(Y;15)(q12;p13) rearrangement in a dizygotic twin pregnancy and (2) the fourth report of the t(Y;15) inherited from maternal origin to date. In contrast with previously reported t(Y;15) translocations, which were mostly of paternal origin [789], (3) we determined the precise breakpoints on both chromosomes and provided more comprehensive genetic information about der(15)t(Y;15) translocation to the parents in the prenatal stage.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, this study constitutes (1) the first reported case of a der(15)t(Y;15)(q12;p13) rearrangement in a dizygotic twin pregnancy and (2) the fourth report of the t(Y;15) inherited from maternal origin to date. In contrast with previously reported t(Y;15) translocations, which were mostly of paternal origin [789], (3) we determined the precise breakpoints on both chromosomes and provided more comprehensive genetic information about der(15)t(Y;15) translocation to the parents in the prenatal stage.…”
Section: Discussionmentioning
confidence: 91%
“…It was reported that one azoospermia male patient had been performed cytogenetic analysis, the karyotype showed 46, XY,t(Y;1)(cen-q11; cen-p11),(Y;15)(q12;p11), and further it was found his mother carried 46,XX,t(Y;15)(q12;p11) [10]. Recurrent spontaneous abortion was also reported in a male partner carried a der(15)t(Y;15) (q12;p12) [5]. In the present report, couple A had twice abortions, while the male carrier of couple B is asthenozoospermia.…”
Section: Discussionmentioning
confidence: 97%
“…These carriers of der(15)t(Y;15)(q12; p11) translocations usually have normal phenotype with unaffected fertility, therefore usually used to called variants [4]. However, some reports found that der(15)t(Y;15)(q12; p11) carriers could have abnormal phenotype like infertility, repeated spontaneous abortion, stillbirths, liveborn children with defects [5,6]. These researches showed genetic counseling and early prenatal prevention were very important when these patients hoped for obtaining normal children.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, carriers of der(15)t(Y;15)(q12; p11) translocations usually have normal phenotype with unaffected fertility and were usually called variants[4] until it was shown that such carriers could have infertility, repeated spontaneous abortion, stillbirths, or liveborn children with defects. [56]…”
Section: Introductionmentioning
confidence: 99%